2020
DOI: 10.25273/jipm.v8i2.5145
|View full text |Cite
|
Sign up to set email alerts
|

Development of Comic Mathematics Learning Media Based on Contextual Approaches

Abstract: <p>The development of teaching materials or instructional media that are tailored to the characteristics of students is considered important at this time. For this reason, this study aims to develop comic-shaped mathematics learning media based on a valid and practical contextual approach. This comic was developed based on the stages of the ADDIE development model. Based on the analysis of the data, it was concluded that this comic based contextual approach was valid and was practically used. This contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
1
4
0
10
Order By: Relevance
“…The students' suggestions for the betterment of the app may support this rating. Results show similarities with Nurdin et al (2020) study, where the students rated the contextually based comics above the practicality criteria. The authors concluded that comics could be an effective medium for mathematics learning.…”
Section: Resultssupporting
confidence: 68%
“…The students' suggestions for the betterment of the app may support this rating. Results show similarities with Nurdin et al (2020) study, where the students rated the contextually based comics above the practicality criteria. The authors concluded that comics could be an effective medium for mathematics learning.…”
Section: Resultssupporting
confidence: 68%
“…Penyusunan bahan ajar digital dan penentuan layout disesuaikan dengan karakteristik modul yaitu dapat digunakan secara mandiri dan memberikan kemenarikan (Sari&Raharjo: 2018). Salah satu media pembelajaran yang dinilai mampu untuk menarik minat baca siswa adalah komik, berdasarkan hasil penelitiannya bahwa komik yang didesain adalah komik berbasis pendekatan kontekstual (Nurdin et al, 2020) namun bahan ajar yang sering kali dikembangkan adalah bahan ajar yang bersifat konvesional artinya mudah sobek, berat dan tentunya karena bahan ajar konvensional tidak menarik minat baca siswa. Maka penelitian ini perlu adanya inovasi baru dalam penyusunan bahan ajar matematika berbasis komik digital.…”
Section: Pendahuluanunclassified
“…Comics as a medium that focuses more on images must have a high percentage of content feasibility. Accurate images in comics according to the storyline will increase student motivation [19].…”
Section: Resultsmentioning
confidence: 99%